1996
DOI: 10.1103/physrevb.53.12566
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia as an active doping source gas of hydrogenated amorphous germanium films

Abstract: In this work the electrical properties of nitrogen-doped hydrogenated amorphous germanium films ͑a-Ge:H͒ using ammonia ͑NH 3 ͒ as a gaseous doping source are reported. The results are compared with those of N-doped a-Ge:H films using N 2 as a source gas. The doping mechanisms appear to be similar in both cases. However, the doping efficiency of NH 3 is smaller than that of N 2 . The use of NH 3 also induces a very large topological disorder. The present results give support to the view that active N doping in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
5

Year Published

1998
1998
1999
1999

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
3
0
5
Order By: Relevance
“…For example, it has been argued that NH and NH 2 atomic configurations, which are expected to occur in the network due to the preferential attachment of H to N, may be an important source for the observed increased disorder. 5 The present article reports on the structural changes induced by the incorporation of nitrogen in the a-Ge:H network as monitored by infrared ͑IR͒ spectroscopy. In order to be able to detect N-H bonds by this technique, a-Ge͑N͒:H samples having nitrogen concentrations (C N ) between 2 and 6 at.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, it has been argued that NH and NH 2 atomic configurations, which are expected to occur in the network due to the preferential attachment of H to N, may be an important source for the observed increased disorder. 5 The present article reports on the structural changes induced by the incorporation of nitrogen in the a-Ge:H network as monitored by infrared ͑IR͒ spectroscopy. In order to be able to detect N-H bonds by this technique, a-Ge͑N͒:H samples having nitrogen concentrations (C N ) between 2 and 6 at.…”
Section: Introductionmentioning
confidence: 98%
“…These studies have shown that, for C N Ͻ1%, N exhibits normal doping behavior, similar to other traditional dopant impurities, including augmented disorder and defect density. [3][4][5] However, the details of the structural modifications introduced by N in a-Ge:H are still an open question. For example, it has been argued that NH and NH 2 atomic configurations, which are expected to occur in the network due to the preferential attachment of H to N, may be an important source for the observed increased disorder.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] As part of this research effort, n-and p-type doping studies of a-Ge:H have been undertaken by our group, using different elements of columns III and V of the Periodic Table as dopant species. [6][7][8][9][10][11][12][13] The measurement of the photoconductivity ͑PC͒ is a valuable tool to investigate the recombination processes and the distribution of deep defect states in the mobility gap of amorphous semiconductors. In particular, the dependence of the PC on the position of the Fermi level (E F ) in doped samples, provides information on the recombination processes of electrons and holes, as E F moves toward the band edges.…”
Section: Introductionmentioning
confidence: 99%
“…Recentemente, progressos na obtenção do germânio amorfo com qualidade eletrônica [11][12][13] têm aumentado o interesse neste material. Desta forma, têm sido desenvolvido diversos estudos sobre este material [12,[14][15][16][17][18][19][20][21][22][23].…”
Section: Motiva Cãounclassified
“…Recentemente, progressos na obtenção do germânio amorfo com qualidade opto-eletrônica [11][12][13] têm aumentado o interesse neste material. Desta forma, múltiplos estudos estão sendo desenvolvidos, desde as propriedades a nível de dopagem [12,[14][15][16][17][18][19], utilizando tanto elementos da coluna III como da coluna V, até estudos com ligas, utilizando elementos tais como, nitrogênio, carbono e estanho [20][21][22][23].…”
Section: Introducãounclassified